Detectors in High-Energy Physics Experiments Underlying Physics, Working Principles, and Realizations - Eigen, Gerald; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access textbook explores the physics of detectors used in high-energy physics and heavy ion physics experiments. In addition to presenting fundamental principles, physics laws, and working techniques, the author delves into various subdetectors, summarizing their properties. These include gaseous detectors, semiconductor vertex detectors, calorimeters, photodetectors, and complete experimental setups. The aim is to provide students with a comprehensive understanding of state-of-the-art technologies in the field. Intended for master's and early PhD students in physics, the book requires a basic knowledge of mechanics, quantum mechanics, electrodynamics, statistics, and particle physics. Each chapter is enriched with exercises designed to deepen the reader's understanding of the material.
Introduction -- Interactions of Charged Particles and Photons with Matter and Fields -- Measurements of Energy Loss of Charged Particles -- Gaseous Tracking Detectors -- Momentum Measurements -- Detectors for Vertex Measurements -- Detectors for Energy Measurements -- Photodetectors, Plastic Scintillators and Time Measurements -- Particle Identification Techniques and Devices -- Trigger and Data Acquisition -- Examples of Full Detector Systems.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Particles (Nuclear physics).; Nuclear physics; Particle accelerators; Medical physics; Quantum physics; Particle Physics; Nuclear Physics; Accelerator Physics; Medical Physics; Quantum Measurement and Metrology